P487 Changing patterns in pressor support in the neonatal intensive care unit. a ten-year overview. (June 2019) - Chathasaigh, Caitríona Ní; Corderroura, Montse; John, Prof; Murphy, F
Abstract : Background & Aims: Haemodynamic instability is a problem frequently encountered in Neonatal Intensive Care. It is a relatively common complication of preterm birth. In term neonates, it is often associated with significant disease processes such as pulmonary hypertension and sepsis. Infants with low blood pressure are usually treated with fluids, inotropes and occasionally steroids, in cases of refractory hypotension. The aim of treating hypotension is to preserve adequate end-organ perfusion and to avoid low cerebral blood flow which in premature infants can be associated with Intra-Ventricular Haemorrhage, Periventricular Leukomalacia and ultimately adverse neuro-developmental outcomes. The objective of this study, was to determine the pattern of inotrope and vasopressor use at a tertiary care Neonatal Intensive Care Unit (NICU) over a ten-year period from 2008 to 2017. Methods: We conducted a retrospective cross-sectional study over a ten-year period. The data gathered included the number of vials of dopamine, dobutamine, adrenaline, noradrenaline and hydrocortisone registered by the Pharmacy department to the NICU. From these figures, we extrapolated the pattern of pressor usage. We also reviewed the pattern of surfactant and antenatal steroid administration. Results: This study highlights that dopamine remains the first-line agent, regardless of the clinical scenario. Dobutamine is less commonly used, but figures remain high. An increase in endogenous catecholamine usage in 2013–2015 is apparent, with the administration of hydrocortisone tapering off in recent years. Rates of surfactant administration have decreased since 2013, coinciding with an ongoing upward trend in antenatal steroid administration to women up to 33 completed weeks of gestation Discussion: Low systemic blood flow is commonly encountered in extremely premature infants. Despite this, it remains unclear what the safest and most effective drug is to prevent and manage hypotension. Few controlled trials have directly compared the individual agents and the effects that these drugs have on any meaningful outcome. As such, the database with the highest level of medical evidence, the Cochrane Library has come to few solid clinical recommendations. Conclusion: Despite the ongoing upward trend in admissions to NICU, inotrope and vasopressor use is falling. We hypothesise that this reflects an overall improvement in the management of newborns, as pressor agents act as a surrogate marker of a baby's underlying condition. Through the judicious use of antenatal steroids, greater attention to initial resuscitation, early initiation of CPAP and early extubation, survival rates are improving, incidence of Cystic PVL is falling and overall morbidity is down